Teachers' changing practices with information and communication technologies: an up-close, longitudinal analysis - Joanne Orlando (Association for Learning Technology, 2014)
While digital technology has become a significant resource for contemporary schooling, we still have little understanding of how these resources shape teachers' scholarly practices and what support is needed to improve and move forward. This paper reports on a 5-year qualitative, longitudinal study on the scholarly practices of a small number of Australian primary and secondary school teachers in their use of digital technology. The study aimed to understand the complexity of their changing practices. Four categories of change were evident in the teachers' practice with digital technology over time: knowledge, learning organisation, pedagogy and core approaches to teaching. The changes each teacher demonstrated reflected their distinct knowledge sets and beliefs. Tracing their changes longitudinally showed that some teachers demonstrated faster and more consistent change in their practices with digital technology than others and that visible change in their practices was not evident over the short term. This study highlights that change in digital scholarship is a personal and complex process and worthy changes are those that meaningfully respond to the context and also contribute to the teachers' commitment to reflection and renewal of practice. Significant support is therefore that which provides the space and opportunity for teachers' individualised professional understandings and aspirations to be acknowledged and built on.